Dynamic Bonus Pools - Budde, Jörg; Hofmann, Christian (The Accounting Review, 2024)
ABSTRACT We study the properties of long-term bonus pools (BPs) with rollover provision in a multiperiod moral hazard setting, where the principal uses subjective information to privately assess the agent’s performance and the agent is protected by limited liability (LL). To provide incentives, the principal funds a multiperiod BP with a fixed payment that may be distributed over time to the agent and a third party. We find that the optimal long-term BP contract features performance targets that are contingent on past performance. Specifically, high subjective performance implies an easy target, and low subjective performance implies a difficult target. To implement the long-term BP contract, the principal provides nondichotomous performance reports. The study contributes to the literature that discusses the mechanisms that make subjective performance information useful for incentive contracting. JEL Classifications: D82; M52; M54.